Chasing digital : a playbook for the new economy - Stevens, Anthony; Strauss, Louis (John Wiley & Sons Australia, Ltd, 2018)
Not every company is born digital. For every smart young tech-head in a digital disruptor, a hundred chief executives are wringing their hands over how to drag their enterprise into the digital age. Chasing Digital speaks directly to these leaders and provides a roadmap for change that they desperately seek. By linking new technologies to familiar business strategies, this book will become a game-changer in leadership thinking in digital times.